ANALISIS PELAYANAN ANGKUTAN UMUM MINIBUS JUMBO TRAYEK KOTA LANGSA-KOTA LHOKSEUMAWE - Rusli Rusli; Sofyan M. Saleh; Renni Anggraini (Jurnal Arsip Rekayasa Sipil dan Perencanaan, 2018)
The Langsa City is connected to the Lhokseumawe city which is both of the city is the most strategic area for the central business and trading activities. To support the connection between the cities, the transportation infrastructure and public transport play very important role. In this case, jumbo minibus and terminal building are needed to evaluate to gain the better level of service public transport. Therefore, the goal of this study is to evaluate the level of service of the jumbo minibus as the most convenience to serve Langsa City - Lhokseumawe route by using standard service indicator approach. The data were collected using onboard survey and off-board survey. Collected data then use to analyze and assess the level of service of this public transport. Level of service assessment of public transport which used in this study refers to the indicators which issued by Directorate General of Land Transportation. The form of the level of service is consist of several indicator such as load factor in peak hour, load factor in an off-peak hour, travel speed, headway of travel time, services time, frequency, number of the vehicle in operation, waiting time for passengers, the beginning, and end of time served. The result from the analysis shows that the total value obtained from all indicators is about 20. Based on the Directorate General of Land Transportation approach is recommended that the level of service of the jumbo bus is in good criteria. However, some parameters are still classified as less good criteria. Thus, it needs to improve some indicators of the level of service by considering less significant criteria.